Results of neurotrophic keratopathy treatment by direct corneal neurotization - M.B. Gushchina; S.B. Butsan; V.Yu. Sergeeva; K.S. Salikhov; A.V. Tereshchenko; E.V. Erokhina; S.A. Mal’kov (Офтальмохирургия)
Relevance. Trigeminal nerve defeat can lead to the development of neurotrophic keratopathy. The only pathogenetically justified method of treating this pathology is corneal neurotization. Purpose. To develop rehabilitation tactic for the patients with neurotrophic keratopathy based on the analysis of the results of operations performed according to the author’s technique of direct corneal neurotization. Material and methods. 10 direct corneal neurotizations: with initial manifestations – in 2 cases and in the advanced stage of neurotrophic keratopathy – in 8 cases. Results and discussion. Postoperative period proceeded without complications. Corneal sensitivity was restored in 60%. In all cases, corneal transparency improved, the density of the eyesore and the depth of the invasion of opacities decreased, subbasal nerve fibers began to be visualized, positive dynamic in the state of tear production were observed. Perforation defects of the cornea was closed. In initial stage of the disease corneal opacity has almost completely regressed. Conclusion. Direct corneal neurotization provides restoration of its sensitivity, prevention of neurotrophic keratopathy, which provides medical and social rehabilitation.